Pengaruh Kepemimpinan Demokratis, Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Dinas Tenaga Kerja Dan Transmigrasi Provinsi Kalimantan Tengah - Crysma Sagita Saragih; Anike Retawati; Indah Nur Oktavia; Nurlia Eka Damayanti (Jurnal Economic Resource, 2026)
This study aims to analyze the effect of democratic leadership, work discipline, and work environment on e mployee performance at the Manpower and Transmigration Office of Central Kalimantan Province. This research employed a quantitative approach using a survey method involving 62 respondents selected through purposive sampling. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that democratic leadership, work discipline, and work environment have a positive and significant effect on employee performance. These findings suggest that improving leadership quality, strengthening work discipline, and creating a supportive work environment can enhance employee performance. This study is expected to provide practical insights for government institutions in improving employee performance.